Using Artificial Intelligence in the Learning Process - Umarova Nigora Alisherovna; Ibragimov Nukhriddin Madazimovich; Kholisov Alisher Farkhodovich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Artificial Intelligence (AI) is increasingly transforming the educational landscape by enabling personalized, adaptive, and efficient learning experiences. This paper explores the role of AI technologies in enhancing the learning process through intelligent tutoring systems, adaptive content delivery, automated assessment, and data analytics. By reviewing recent advancements and practical implementations, the study highlights how AI can improve learner engagement, optimize educational outcomes, and support educators. The paper also discusses key challenges such as data privacy, ethical considerations, and equitable access to technology. Finally, future directions for research and development are proposed to ensure responsible and effective integration of AI in education.